2022
DOI: 10.2991/aebmr.k.220204.033
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Service Quality on Perceived Trust Moderated by Digital Technology at PT. Pupuk Indonesia

Abstract: This study aims to see the effect of the interaction quality, outcome quality, and environmental quality on customer perceived value moderated by digital technology and affects consumer trust. The company's object in this research is PT Pupuk Indonesia Tbk, with the respondents being farmer groups and cooperatives who place orders for subsidized fertilizers produced by the company. The form of this research is quantitative research by distributing questionnaires. Questionnaires will be distributed with a minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Mara & Hutabarat (2022). [16] The repayment performance of the business will be negatively impacted by the entrepreneur's lack of entrepreneurial competencies, the co-founders' lack of ability and skills, and the entrepreneur's lack of a proper education. The borrower's proper education level has a favourable effect on their ability to make payments.…”
Section: Word Of Mouth Communicationmentioning
confidence: 99%
“…Mara & Hutabarat (2022). [16] The repayment performance of the business will be negatively impacted by the entrepreneur's lack of entrepreneurial competencies, the co-founders' lack of ability and skills, and the entrepreneur's lack of a proper education. The borrower's proper education level has a favourable effect on their ability to make payments.…”
Section: Word Of Mouth Communicationmentioning
confidence: 99%
“…According to Lewis (1993); Mara & Hutabarat (2022), revealed that high service quality will lead to better customer satisfaction which in turn has an impact on future income levels. For this reason, many companies are trying to have superior service quality in order to be a leader in an increasingly fierce market competition (Lovelock & Wirtz, 2011).…”
Section: Literature Review Service Qualitymentioning
confidence: 99%